Assessment of advanced clinical practitioners. Issue 6 (2nd November 2022) - Wallis, Lucy; Locke, Rachel; Sutherland, Clare; Harden, Beverley
ABSTRACT: To continue growing the advanced clinical practitioner (ACP) role nationally, and similar roles internationally, there must be widely held trust in the level of practice and the roles worked in service by ACPs. This requires infrastructure to support ACPs through their training and ensure they are fit to qualify. This short report focuses on an evaluation of assessment processes in the acute sector in a county in England, to understand their feasibility and suitability. The qualitative research design was attendance at assessment panels and 17 semi-structured interviews with assessors and ACP trainees, from nursing, physiotherapy, paramedicine and operating department practice backgrounds based at two hospitals. Key themes identified through thematic analysis were the different approaches to assessment and the support required to engage effectively with assessment. One hospital had a well understood process, including ACPs with a clear identity. The other hospital had a credible assessment process that continues to be developed. The insights from this study enabled lessons to be drawn for those responsible for workforce development who are key to the future development of the ACP role and to ensure high standards of interprofessional care.